Human Safety Evaluation of Heavy Metals, Physicochemical Parameters, and Microorganisms in Lagoon Water at Ikorodu Lighter Terminal in Lagos, Nigeria - Yahaya, Tajudeen; Balogun, Khadijat; Danlami, Mohammed Bashar; Shemishere, Ufuoma; Abdulganiyu, Yunusa; Ola-Buraimo, Olatunji (Tecno Scientifica Publishing, 2023)
Ikorodu Lighter Terminal is an important lagoon port in Lagos, Nigeria. However, the intense anthropogenic activities that take place around the port could potentially pollute the water. This study assessed the safety of human exposure to the water around the port. Samples of the water were assayed for physicochemical parameters, namely: electrical conductivity, biochemical oxygen demand (BOD), total suspended solids (TSS), total dissolved solids (TDS), pH, turbidity, hardness, calcium, chloride, sulphate, nitrite, and phosphate. Moreover, heavy metals, including lead, manganese, copper, cadmium, nickel, and chromium, were analyzed, and their values were used to estimate potential health risks. Also assayed was the presence of microorganisms. The water samples had non-permissible levels of nitrite, oil and grease, and BOD. The concentrations of the heavy metals as well as their average daily ingestion and average daily dermal exposure were within the tolerable limits, except Ni. However, their hazard quotient and carcinogenic risk via ingestion and dermal contact exceeded the tolerable limits. Safe levels of bacteria, coliforms, and fungi were detected in the water. Based on these results, the water may expose users to health hazards. There is a need for policies geared towards the safety of human exposure to the water.